2021
DOI: 10.1016/s2468-2667(20)30210-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between pre-pregnancy psychosocial risk factors and infant outcomes: a population-based cohort study in England

Abstract: Summary Background Existing studies evaluating the association between maternal risk factors and specific infant outcomes such as birthweight, injury admissions, and mortality have mostly focused on single risk factors. We aimed to identify routinely recorded psychosocial characteristics of pregnant women most at risk of adverse infant outcomes to inform targeting of early intervention. Methods We created a cohort using administrative hospital data (Hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 30 publications
1
54
0
Order By: Relevance
“…Although a study linking the effects of PCC in improving pregnancy outcomes was inconclusive, it revealed a relationship between PCC education and counselling with improved knowledge and control of risky behaviours [18]. Several psychosocial risk factors such as teenage birth, history of mental health, behavioural conditions, and living in deprived areas were associated with low birth weight and other adverse infant outcomes [19], which can be prevented through PCC.…”
Section: Introductionmentioning
confidence: 99%
“…Although a study linking the effects of PCC in improving pregnancy outcomes was inconclusive, it revealed a relationship between PCC education and counselling with improved knowledge and control of risky behaviours [18]. Several psychosocial risk factors such as teenage birth, history of mental health, behavioural conditions, and living in deprived areas were associated with low birth weight and other adverse infant outcomes [19], which can be prevented through PCC.…”
Section: Introductionmentioning
confidence: 99%
“…Specific socioeconomic, behavioral, and clinical characteristics of pregnant women might make them more vulnerable to violence [ 9 ]. Health care services should respond proactively to pre-pregnancy psychosocial risk factors, and interventions should be multifaceted, delineate different types of violence, control for measurement reactivity, and design a tailored intervention program adjusted to the specific needs of couples experiencing interpersonal violence [ 11 , 12 , 58 ]. All mental health care professionals referring a woman to a maternity service should ensure that they communicate complete information on any past and present mental health problem.…”
Section: Discussionmentioning
confidence: 99%
“…Many adverse outcomes are associated with domestic violence during pregnancy: higher rates of preterm and low birth weight, poor reproductive health, unintended pregnancy, planned and spontaneous abortion, postnatal depression, and substance abuse [ 10 ]. A large population-based cohort study on more than 2 million mother–baby pairs in the UK showed that pre-pregnancy psychosocial risk factors (i.e., previous birth before 20 years of age, hospital contacts related to adversity or mental health or behavioral conditions, and deprivation) were associated with substantially increased risks of low birth weight, preterm birth, injury, and death during the 12 months from postnatal discharge [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…37 The 20-week minimum cutoff before birth avoided exclusion of extreme preterm births and captured pre-birth data for the full cohort. 40 This study was approved by the UK Medicines and Healthcare products Regulatory Agency Independent Scientific Advisory Committee (19_162R), under Section 251 (NHS Social Care Act 2006), for the use of anonymised records in research without individual participant written consent.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%